Viral G protein-coupled receptors as modulators of cancer hallmarks. (June 2020) - van Senten, Jeffrey R.; Fan, Tian Shu; Siderius, Marco; Smit, Martine J.
Graphical abstract: Abstract: Herpesviruses encode transmembrane G protein-coupled receptors (GPCRs), which share structural homology to human chemokine receptors. These viral GPCRs include KSHV-encoded ORF74, EBV-encoded BILF1, and HCMV-encoded US28, UL33, UL78 and US27. Viral GPCRs hijack various signaling pathways and cellular networks, including pathways involved in the so-called cancer hallmarks as defined by Hanahan and Weinberg. These hallmarks describe cellular characteristics crucial for transformation and tumor progression. The cancer hallmarks involve growth factor-independent proliferation, angiogenesis, avoidance of apoptosis, invasion and metastasis, metabolic reprogramming, genetic instability and immune evasion amongst others. The role of beta herpesviruses modulating these cancer hallmarks is clearly highlighted by the proliferative and pro-angiogenic phenotype associated with KSHV infection which is largely ascribed to the ORF74-mediated modulation of signaling networks in host cells. For HCMV and Epstein-Bar encoded GPCRs, oncomodulatory effects have been described which contribute to the cancer hallmarks, thereby enhancing oncogenic development. In this review, we describe the main signaling pathways controlling the hallmarks of cancer which are affected by the betaherpesvirus encoded GPCRs. Most prominent among these involve the JAK-STAT, PI(3)K-AKT, NFkB and MAPK signaling nodes. These insights are important to effectively target these viral GPCRs and their signaling networks in betaherpesvirus-associated malignancies.